Association between equivalent current dipole source localization and focal cortical dysplasia in epilepsy patients - Blenkmann, Alejandro Omar (2012)
We analysed the association between focal cortical dysplasia (FCD) visible in MRI and the location of equivalent current dipole (ECD) of single interictal scalp EEG spikes (IIS) in 11 epilepsy patients. We calculated several indicators of distance of ECDs to the FCD border. The results confirm some previous studies suggesting that the epileptogenic zone associated to the location of ECDs extends beyond the FCD visible in MRI. The analysis suggests the ECDs to be in a shell parallel to part of the FCD surface.